Lesbian studies : setting an agenda - Wilton, Tamsin (Routledge, 1995)
An academic approach to both gender and the erotic, which clarifies the damaging influence of heterosexism and examines Lesbian treatment in sociology, psychology, social policy, cultural studies, film theory and history.